The Effect of Pasak Bumi (Eurycoma longifolia, Jack) Roots Ethanol Extract against Hematology Profile of Healthy Volunteers - Laela Hayu Nurani; Fara Azzahra; Sitarina Widyarini; Abdul Rohman (Faculty of Pharmacy, Universitas Gadjah Mada, 2019)
The roots of Eurycoma longifolia, Jack has a lot of beneficial activity on human health. The use of Eurycoma longifolia, Jack roots as a traditional medicine should be made in the form of a dosage that is more effective, safe, and had no side effects, especially on hematology. Easy preparations are capsule. This study aimed at identifying the effect of ethanol extract capsule of Eurycoma longifolia, Jack roots on hematology of healthy volunteers. Healthy volunteers were assigned in the study, each of which were 10 male and 10 female who met the inclusion criteria. Both groups were given ethanol extract capsule of Eurycoma longifolia, Jack roots for 14 days, with the dose of 300 mg extract once a day, after meal, at night. Hematology examination was performed on day 0; 14 and 42. Results were compared statistically using Repeated ANOVA and Friedman tests. The result of the study indicated that the average value of hematology at the examination day of 0; 14; and 42, there were significant differences in MCV and leukocyte parameters in healthy male volunteers (p<0.05). MCH, LED and monocyte parameters in healthy female volunteers had a significant difference of (p<0.05). However, the parameter values were still within the normal range. Monitoring results showed that some of the side effects were frequent urinary, dizziness, nausea, sweating, insomnia, and increasing appetite on healthy male volunteers. Meanwhile, on healthy female volunteers, there were frequent urinary, insomnia, constipation. Having ethanol extract capsule of the Eurycoma longifolia, Jack roots did not affect the hematology parameters of healthy male and female volunteers, but it caused some side effects.